A LINGUOCULTUROLOGICAL ANALYSIS OF ITALIAN PROVERBS RELATED TO THE CONCEPTS OF GOOD AND EVIL - Sadikova Bahora Maxmurovna (Web of Journals Publishing, 2025)
This article explores the linguoculturological features of Italian proverbs that convey the concepts of good and evil. Proverbs, as condensed expressions of collective wisdom, reflect the values, beliefs, and moral judgments of a given culture. By analyzing a selection of Italian proverbs, the study examines how notions of virtue and vice are linguistically encoded and culturally interpreted. The research adopts a qualitative method, focusing on semantic, cultural, and contextual aspects of the proverbs. The findings highlight the symbolic representations of good and evil in Italian linguistic tradition, revealing the role of proverbs in shaping ethical perspectives and social behavior. This study contributes to a deeper understanding of the relationship between language and culture, particularly in how moral concepts are transmitted through idiomatic expressions in everyday communication.
Keywords: Italian proverbs, good and evil, linguoculturology, moral values, cultural semantics, figurative language, paremiology, ethical concepts, language and culture, proverbs analysis.